Mucosal-associated invariant T-cells: new players in anti-bacterial immunity. - Ussher, J; Klenerman, P; Willberg, C (Frontiers Research Foundation, 2014)
Mucosal-associated invariant T (MAIT) cells are an innate-like T-cell population involved in anti-bacterial immunity. In human beings, MAIT cells are abundant, comprising ~10% of the CD8(+) T-cell compartment in blood. They are enriched at mucosal sites and are particularly prevalent within the liver. MAIT cells are defined by the expression of a semi-invariant T-cell receptor (Vα7.2-Jα33/12/20) and are restricted by the non-polymorphic, highly evolutionarily conserved MHC class Ib molecule, MHC-related protein (MR)1. MR1 has recently been shown to present an unstable pyrimidine intermediate derived from a biosynthetic precursor of riboflavin; riboflavin biosynthesis occurs in many bacteria but not in human beings. Consistent with this, MAIT cells are responsive to riboflavin-metabolizing bacteria, including Salmonella. In mouse models, MAIT cells have been shown to play a non-redundant role in anti-bacterial immunity, including against Escherichia coli, Klebsiella pneumoniae, and Mycobacterium bovis BCG. In human beings, MAIT cells are decreased in frequency in the blood of patients with tuberculosis or pneumonia, and their frequency has been inversely correlated with the risk of subsequent systemic bacterial infection in patients in intensive care. Intriguingly, MAIT cells are also depleted from the blood early in HIV infection and fail to recover with anti-retroviral therapy, which may contribute to the susceptibility of patients infected with HIV to certain bacterial infections, including non-typhoidal Salmonella. In this review, we will discuss what is currently known about MAIT cells, the role that Salmonella has played in elucidating MAIT cell restriction and function, and the role MAIT cells might play in the control of Salmonella infection.